2007
DOI: 10.1111/j.1750-3841.2007.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Process Parameters on Quality Changes of Shrimp During Drying in a Jet‐Spouted Bed Dryer

Abstract: The objective of the present study was to investigate the effects of various parameters, that is, concentration of salt solution (2%, 3%, 4%[w/v]), boiling time (3, 5, 7 min), drying air temperature (80, 100, 120 degrees C), and size of shrimp, on the kinetics of drying and various quality attributes of shrimp, namely, shrinkage, rehydration ability, texture, colors, and microstructure, during drying in a jet-spouted bed dryer. In addition, the effects of these processing parameters on the sensory attributes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
48
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 16 publications
(18 reference statements)
13
48
0
1
Order By: Relevance
“…The boiled shrimp was then introduced to a jet spouted bed dryer (Niamnuy et al, 2007a). An initial static bed height was set to be around 25 cm.…”
Section: Boiling In Salt Solution and Dryingmentioning
confidence: 99%
See 1 more Smart Citation
“…The boiled shrimp was then introduced to a jet spouted bed dryer (Niamnuy et al, 2007a). An initial static bed height was set to be around 25 cm.…”
Section: Boiling In Salt Solution and Dryingmentioning
confidence: 99%
“…Tapaneyasin et al (2005) and Niamnuy et al (2007a) indeed studied the effects of the size of shrimp as well as that of the inlet air temperature on the color changes of shrimp dried in a jet spouted bed dryer. It was found that the size of shrimp and inlet air temperature significantly affected the color changes of dried shrimp and the use of a constant inlet air temperature of 100-120°C yielded dried shrimp of higher redness value.…”
Section: Introductionmentioning
confidence: 99%
“…This observation was in disagreement with work of Viskelis et al (2011) who reported an increase in metric chroma values of apples during storage. Development of redness on exposure of shrimp meat to heat and/or gamma radiation is as a result of the release of astaxanthin when carotenoproteins breakdown during protein denaturation (Niamnuy et al, 2007;Akonor et al, 2016).…”
Section: Results Of Metric Chroma (C) Hue Angle Andmentioning
confidence: 99%
“…However, texture indexes were positively affected by increasing the air-drying temperature probably because of changes in food protein matrix. Niamnuy et al (2007) studied the drying process of shrimps in a jet-spouted bed dryer. The effect of various parameters (concentration of salt, size, cooking time, and drying air temperature) was investigated upon the kinetics of drying and various quality attributes of shrimps during drying.…”
Section: Introductionmentioning
confidence: 99%